Distribution center facility: resource utilization and optimization study (development of an approach) - Yap, Seck Koon. (2008)
This study looks the capacity and resource planning for a selected company. The aim is to examine and find out the optimal machines to deploy in relation to the warehouse occupancy and activity levels.